Seawater Opportunities to Increase Heating, Ventilation, and Air Conditioning System Efficiency in Buildings and Urban Resilience - Schibuola, Luigi; Tambani, Chiara; Buggin, Antonio (Frontiers in Energy Research, 2022)
In coastal cities, seawater heat pumps (SWHPs) can combine heat pump technology with the availability of seawater to produce the heat and the cold necessary for heating, ventilation, and air conditioning (HVAC) systems installed in buildings. In heating mode, the seawater is used as a cold source and provides the low-temperature heat needed for the operation of the machine. In cooling mode, the seawater removes the heat dissipated by the condenser of the heat pump working for air conditioning. This seawater application seems to be very promising since the temperature trend of the seawater appears to be more favorable than the alternative use of outdoor air, both in winter and in summer. In a case study in Trieste, the performance of a district heating/cooling network supplied with seawater and based on decentralized heat pumps is investigated. For this purpose, annual dynamic simulations were performed, modeling an urban area, the heat pumps, and the network. The energy efficiency evaluation shows a clear superiority of the SWHP solution compared to boilers and airsource heat pumps and thus the possibility to provide a significant contribution to the decarbonization of buildings. Moreover, the results highlight the ability of this GWHP network to reduce the urban heat island (UHI) phenomenon since the heat dissipated by the heat pumps during summer air conditioning is removed from the urban area. Therefore, SWHPs in coastal cities can be among the mitigation measures for UHI to increase outdoor comfort and heat wave resilience in urban areas.